2019
DOI: 10.1051/matecconf/201929011004
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Gaseous Fuels from Agricultural Waste Pyrolysis (Part I)

Abstract: The study, presented in two parts, puts in discussion the experimental results of low and high temperature pyrolysis on agricultural residues using a tubular batch reactor. During the experiment, nitrogen was used both as reaction environment and gas products carrier. The work focusses mainly on the pyrolysis gas analytical composition resulted from the process. The first part of the research is dedicated to the effect of process low temperature on rape straw pyrolysis. The experiments were conducted at 300°C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…The experiments were carried out in a fed-batch reactor under nitrogen atmosphere. The data referring to experimental pyrolysis methods applied to the current research study have already been detailed by Ionescu et al [32]. Therefore, here, only the obtained results concerning the gaseous phase (obtained following the process of the pyrolysis of willow wood at a temperature of 800 • C) will be presented and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were carried out in a fed-batch reactor under nitrogen atmosphere. The data referring to experimental pyrolysis methods applied to the current research study have already been detailed by Ionescu et al [32]. Therefore, here, only the obtained results concerning the gaseous phase (obtained following the process of the pyrolysis of willow wood at a temperature of 800 • C) will be presented and discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis gases from agricultural waste were investigated at different temperatures. The result of the rape straw residues pyrolysis conversion demonstrated that high temperatures determine an important increase of H2 content in the gas phase, this strongly affecting the energy potential of the pyrolysis gas [13]. The physical properties of the liquid production from pyrolysis of waste plastic bag compared favorably with diesel oil, which shows that it can be used as diesel oil substitution [14].…”
Section: Introductionmentioning
confidence: 99%